The Manufacturing Planning of Installation Series-Parallel Combination Centrifugal Pump Testing Equipment - Edi Widodo; Rizky Dwi Jayanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study discusses the planning in making a centrifugal pump installation with a combination of two series, namely series and parallel. The concept of discussion refers more to the upgrading of the installation system and calculates the estimated processing time needed to test the performance of the results of the installation that has been made. From the results of the research, it was found that for the preparation of series series installation it takes ± 8.5 minutes including the cutting process of materials and component installation, while the time required in making the installation of parallel circuits ± 28 minutes so that the total manufacturing of the two types of series takes 36, 5 minutes. In terms of performance generated from each installation obtained at full aperture where for the series of head series the value obtained is 37.6 m with a flow capacity of 3.25 l / s while for the head value on the parallel pump obtained by 27.7 m with a capacity flow of 3.75 l / s and this pump operates at 2900 rpm. So it can be seen from the results of the head and flow capacity obtained values ​​indicate good pump performance and ready to be used as a practical tool in the laboratory.